Non-linear Analytical Model For Bread-Loaf Permanent Magnet Machine - Sapmaz, Tunahan; Ocak, Oguzhan; Oner, Yasemin (SPRINGER SINGAPORE PTE LTD, 2025)
This paper proposes a non-linear analytical model for bread-loaf permanent magnet (PM) machines, combining magnetic equivalent circuit (MEC) and conformal mapping (CM) techniques. It examines both no-load and on-load conditions for two different machine structures. The fundamental principle of the proposed model is its consideration of winding flux leakage and iron saturation. Additionally, the model is analyzed for two different winding schemes: distributed winding and concentrated winding. An iterative process is implemented to estimate the electromagnetic performance when the stator iron core is saturated under heavy load conditions. Furthermore, this non-linear model sets a standard for bread-loaf PM machines. In conclusion, the accuracy and practicality of the MEC-CM combined model are verified through finite element analysis (FEA) and experimental results.
Keywords: Analytical models; MEC; Non-linear situation; Flux leakage; PM machines; Conformal mapping; FIELD DISTRIBUTION; INDUCTION-MOTOR; OPTIMIZATION; PREDICTION; SYSTEM; Engineering